2011
DOI: 10.1002/jcp.22733
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability in mouse embryonic fibroblasts null for the transcriptional co‐repressor Ski

Abstract: Ski is a transcriptional regulator that has been considered an oncoprotein, given its ability to induce oncogenic transformation in avian model systems. However, studies in mouse and in some human tumor cells have also indicated a tumor suppressor activity for this protein. We found that Ski−/− mouse embryo fibroblasts exhibit high levels of genome instability, namely aneuploidy, consistent with a tumor suppressor function for Ski. Time-lapse microscopy revealed lagging chromosomes and chromatin/chromosome bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Overexpression of c-Ski in cultured avian fibroblasts induces terminal differentiation of muscle cells (Colmenares and Stavnezer 1989), and ectopic expression of c-Ski in various muscle cell lines triggers the expression of muscle-specific genes (Colmenares et al 1991b;Engert et al 1995;Ichikawa et al 1997;Kobayashi et al 2007;Zhang and Stavnezer 2009). In addition to muscle and neuronal lineages, c-Ski modulates the differentiation of hematopoietic cells (Dahl et al 1998a;Pearson-White et al 1995;Ueki et al 2004Ueki et al , 2008 and fibroblasts (Cunnington et al 2011;Jinnin et al 2007;Liu et al 2008;Marcelain et al 2011) in vitro. Notably, the expression of c-Ski is altered under many pathological conditions, including demyelinated or injured peripheral nerves (Atanasoski et al 2004), wound healing (Li et al 2011;Liu et al 2010), liver regeneration (Macias-Silva et al 2002), and skeletal muscle regeneration (Soeta et al 2001).…”
Section: C-ski In Cancer Progressionmentioning
confidence: 98%
“…Overexpression of c-Ski in cultured avian fibroblasts induces terminal differentiation of muscle cells (Colmenares and Stavnezer 1989), and ectopic expression of c-Ski in various muscle cell lines triggers the expression of muscle-specific genes (Colmenares et al 1991b;Engert et al 1995;Ichikawa et al 1997;Kobayashi et al 2007;Zhang and Stavnezer 2009). In addition to muscle and neuronal lineages, c-Ski modulates the differentiation of hematopoietic cells (Dahl et al 1998a;Pearson-White et al 1995;Ueki et al 2004Ueki et al , 2008 and fibroblasts (Cunnington et al 2011;Jinnin et al 2007;Liu et al 2008;Marcelain et al 2011) in vitro. Notably, the expression of c-Ski is altered under many pathological conditions, including demyelinated or injured peripheral nerves (Atanasoski et al 2004), wound healing (Li et al 2011;Liu et al 2010), liver regeneration (Macias-Silva et al 2002), and skeletal muscle regeneration (Soeta et al 2001).…”
Section: C-ski In Cancer Progressionmentioning
confidence: 98%
“…However, participation of Ski in tumorigenesis is more complex as emerging evidence indicates that Ski could also act as a tumor suppressor protein in certain type of cancers [10,11,12,13]. An observation which is consistent with the increased tumour susceptibility observed in Ski deficient ( Ski +/−) mice [14] and the high chromosomal instability found in the Ski knockout (−/−) mouse embryonic fibroblasts (MEFs) [15]. …”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by the co-localization of Aurora A kinase and Ski at the centrosomal level and Ski being a target of Aurora A phosphorylation [47]. Interestingly, a recent report found that mouse embryonic fibroblasts null for Ski exhibit high levels of aneuploidy, the result of defects in chromosome segregation and a weakened spindle assembly checkpoint [48]. These results suggest that Ski not only acts as an oncogene but also has tumor suppressor function in certain situations.…”
Section: Discussionmentioning
confidence: 94%